Hide and seek - Heidsieck, Bernard 1928-2014 ([Verlag nicht ermittelbar], 1971)
An artists’ book by the husband and wife featuring texts by Heidsieck paired with photographs by Janicot, the abstract expressionist painter turned photographer, performance artist, sound poet, and feminist, who in the late 1960s photographed several of her contemporaries including Julien Blaine, William Burroughs, John Cage, John Giorno, Charlotte Moorman, Esther Ferrer, Jean-Jacques Lebel, and others. https://www.theideaofthebook.com/pages/books/349/francoise-janicot-bernard-heidsieck/hide-and-seek?soldItem=true
"De cet ouvrage achevé d'imprimer le 20 Mars 1971 il a été tiré outre les exemplaires ordinaires 50 exemplaires sur papier B F K contenant un frontispice de Françoise Janicot. Ces exemplaires sont justifiés et signés."
Keywords: Künstlerbuch